The Impact of Social Media Marketing, E-Service Quality, and Review Content on Online Purchase Intention Analyzing the Role of Trust in Grab - Achmadi, Kaneshia; Novitasar, Syadela; Usman, Osly (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
In the We Are Social 2020-Digital 2020 Indonesia report as of January 2020, it was revealed that more than 21.7 million people in Indonesia had adopted ride-hailing or ride-sharing services, including the use of the Grab application. In this context, this research aims to examine the factors that influence the trust of Grab application users, by analyzing the influence of Social Media Marketing, E-Service Quality, and Content Reviews on Online Purchase Intentions. The purpose of this research is to explain the relationship between Social Media Marketing (X1), E-service Quality (X2), and Review Content (X3) with Purchase Intention(Y1) in the context of using the Grab application, as well as how Purchase Intention acts as a mediator in this relationship. Additionally, this research will explore how Trust Level (Z1) is influenced by Purchase Intention and other factors in the Grab ecosystem. This research uses quantitative research and a descriptive approach to determine each variable. Empirical results highlight that social media marketing and e-service quality have an influence on purchase intention. However, content reviews do not have a significant influence on purchase intentions, and social media marketing variables, electronic service quality, and content reviews through trust variables do not have an influence on purchase intentions.